Synthesis and characterization of isophorondiamine based epoxy hardeners from aminolysis of PET - L. Karpati; M. Fejer; D. Kalocsai; J. Molnar; V. Vargha (eXPRESS Polymer Letters, 2019)
The solvolysis of poly(ethylene-terephthalate) (PET) is one of the most researched areas in chemical recycling. In this study PET aminolysis with isophorondiamine has been done - in opposition to recent trends - without excess reagent and the raw reaction product was further used without purification. The aminolysis product was thoroughly characterized with nuclear magnetic resonance (NMR) spectroscopy. Isophoronediamine was used as a solvent to prepare amine cross-linker solutions for epoxy resins. The effect of the concentration on the cross-linking reaction and thermomechanical prop¬erties were investigated. The curing reaction was found to be significantly accelerated by the presence of the aminolysis product. Both the ethylene-glycol and the terephthal-amide-diamines have a catalytic effect on the reaction. The glass transition temperature decreased with increasing concentrations of the cross-linker solutions due to the decreasing cross-link density. Thus, raw aminolysis products can be utilized for epoxy curing and are advantageous in modifying slower curing cycloaliphatic cross linker systems.